(3cTa GdXdGe Yf eYfi GdSdGes - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO , agPG JYdjb SejJg HcTa hefg GdSde VO GdMQH bGd JYGdi (B( (3hEf LfMhG ddSde aGLfM dgG (B) (3GdSGdeI eKd GdTGQcI s
(3BNQgG (B:s
(3hdGjLH QO GdSdGe Ydi GdScQGf hdG jSde Ydi GdaGSb hdGHf LGHQ GdCfOdS eYJPQkG Ye de jSde (B: (3dGJYJHf Ydi JQc GdSdGe abO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3ai NRGfI Bd GdLhgQi ai eOjfI fGHdS HadSWjfs
(3fbdJ ef fSNI ecJhHI HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs